The nature of religious language in the Hebrew Bible - a philosophical reassessment - Gericke, J. (Journal for semitics, 2010)
After a cursory introduction to religious language as a philosophical problem the author offers a new error theory to argue that many of the current philosophical conceptual dilemmas ultimately derive from ancient Yahwism's eclectic diachronic transmutations of polytheistic conceptual categories in the formation of monotheistic conceptual metaphors. Thereafter follows a discussion on the metaphorical turn in Biblical Theology suggesting that the prevalent views might not be adequate to the task of philosophically classifying ancient Israelite religious language and happen to be based on a number of anachronistic metaphysical dichotomies. A descriptive reconstruction of some evaluative metaphysical binary oppositions in the metatheistic assumptions of ancient Yahwism precedes the concluding question of whether many philosophical paradoxes regarding the deity-reality relation might not be functionally modelled on the format of an oneirological analogy.